Application of selected 2-methylbenzothiazoles AS cationic photoreactive crosslinkers for pressure-sensitive adhesives based on acrylics. (April 2015) - Czech, Z.; Kabatc, J.; Kowalczyk, A.; Sowa, D.; Madejska, E.
Abstract: Since their introduction half a century ago, acrylic pressure-sensitive adhesives have been successfully applied in many fields. They are used in self-adhesive tapes, label signs, marking films and protective films as well as in medical pharmaceutical applications for plaster, in dermal dosage systems and in a wide range of biomedical electrodes. In the last 15 years or so, the UV technology, especially UV-crosslinking, is well established in the market and allows the production of UV-crosslinkable pressure-sensitive adhesives (PSA) based on acrylics with interesting performance. So much so that the larger manufacturers of pressure-sensitive adhesive materials and their suppliers now use very expensive equipment to study pressure-sensitive adhesive behavior: tack, peel adhesion and shear strength. The balance between adhesive and cohesive strength after the crosslinking process is very important and critical for properties of acrylic PSA in form of self-adhesive films. In this work the cationic UV-crosslinking of acrylic PSA containing epoxy groups in their structure and additionally cationic photoinitiators based on 2-methylbenzothiazoles as photoreactive crosslinkers have been investigated using UV-lamp as ultraviolet sources. The investigated acrylic PSA were synthesized from 80 wt% of butyl acrylate, and 20 wt% of glycidyl methacrylate. The use of selected photoreactive crosslinkers: 1, 5-bis[ N, N ׳-(2-methylbenzothiazolium)]pentane diiodide and 1, 10-bis[ N, N ׳-(2-methylbenzothiazolium)]decane diiodide allows manufacturing of high quality PSA materials with interesting properties, such as high tack, high peel adhesion, and excellent shear strength.